IMPACT OF RUBBER MAT FLOORING ON THE THERMAL COMFORT OF DAIRY CATTLE IN HOT HUMID REGIONS - A. Prasad; V. Vishnu Savanth; K.S. Anil; P.C. Saseendran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was carried out at the dairy sheds at University Livestock Farm, Kerala Veterinary and Animal Sciences University. The temperature difference between concrete and immediate rubber mat flooring was measured at 40 different points at five different times of the day for a week. The readings showed a significant difference with the rubber mat being hotter than the concrete for all times except during the morning reading. During the course of a day, the maximum temperature difference between the two surfaces was 0.95º C recorded at 11.40 AM.